Junk food use and neurodevelopmental and growth outcomes in infants in low-resource settings - Chiwila, Melody K.; Krebs, Nancy F.; Manasyan, Albert; Chomba, Elwyn; Mwenechanya, Musaku; Mazariegos, Manolo; Sami, Neelofar; Pasha, Omrana; Tshefu, Antoinette; Lokangaka, Adrien; Goldenberg, Robert L.; Bose, Carl L.; et al. (Frontiers in Public Health, 2024)
This research study was reviewed for approval by the Institutional Review Board (IRB) of each participating institution. Annual reviews are conducted as per each institution's standard review procedures. The IRBs are registered at OHRP with FWAs. Safety and efficacy analyses are performed at scheduled intervals based upon age (after every 100 infants reached one year of age) and the completion of study participation. Written informed consent for trial participation was obtained from the women, or the parents or guardians of minors, by trained staff.